Ecology of the Sontecomapan Lagoon, Veracruz - Castellanos-Páez, Maria Elena; Esquivel Herrera, Alfonso; Aldeco-Ramírez, Javier; Pagano, Marc (D'Amérique latine, 2018)
Tropical coastal lagoon environments provide a number of ecosystem services, but are threatened by the pressure imposed by human activities and climatic change; these systems are particularly vulnerable because of a high demographic growth. Therefore, the understanding of their ecological behavior and the characterization of lagoon health indicators have attained importance. Under this perspective Mexican (UAM-X) and French (UMRs MIO and MARBEC) researchers have collaborated from 2011 to 2014 as part of one action of the international exchange program ECOS/ANUIES, and chose the Sontecomapan lagoon (at the Mexican state of Veracruz) as a case study. This book provides information of the ecological behavior, water quality indicators, and details of microorganisms and plankton, which due to their short life cycles and their high reactivity to environmental conditions are good.